Edu Lobo: o terceiro vértice - Albuquerque, Mônica Chateaubriand Diniz Pires e (2006)
The very purpose of this paper is to describe Edu Lobo’s trajectory within the Brazilian popular music scenario. From a possible genealogy commenced with Heitor Villa-Lobos, passing through Tom Jobim and finishing with Edu Lobo, this paper will stress the commingled influence of these three composers in adopting a vanguard attitude of rescuing and cultivating traditions. The universalization and development of these traditions resulted in the modern Brazilian Popular music of the XX century. Through the methodology of oral history and based on declarations of renowned composers, musicians, critics and singers, most of them appointed by Edu Lobo himself, this paper analyze the context in which Edu Lobo’s work has been developed.